The STAUT-Reader, making general-purpose texts accessible to deaf - Oliveira, Aníbal C. de; Oliveira, Francisco C. M. B.; Barros, Eudenia M.; Freitas, Adriano T. de; Araujo, Thiago A. C. de; Silva, Lidiane C. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2015)
Deaf students have difficulty in reading texts written in languages whose mode is oral-auditory, such as Portuguese. As users of a signed language, it is harder for them to obtain information contained in books, magazines and newspapers. For this purpose, we have built the STAUT-Reader, an electronic reader, designed to help deaf to read texts written in Portuguese. The tool uses a Rule-Based Machine Translation system to produce output texts in a written representation of Libras, the Brazilian Sign Language. To investigate our proposal, we conducted an experiment using a counterbalanced within-subjects design to evaluate the reading performance of deaf readers using our tool. The results showed to be promising, especially for non-oralized deaf.